Atratividade da carreira docente: um estudo com pedagogas iniciantes. - Fassina, Roseneide (2013)
This paper was based on the question related to the choice of the teaching profession, its attractiveness and how it is perceived amongst beginning teachers of children education. The research question takes us on the reasons why young people choose to teach. The objective is to understand the profession choices of beginning teachers and also understand the perception they have of the pedagogical work they perform. The identification of conceptions of teaching and pedagogy is another of the objectives that this study aims. A bibliographic and field research methodology was used, in which questionnaires were administered to better understand the options and conceptions of beginning teachers. Among the authors consulted for theoretical reasons can be underline the names of Contreras , Tardiff , Charlot , Selma Pimenta, Paulo Freire , Gatti , Libâneo among others that address the chosen themes of this dissertation and allowed to concluded that the teaching profession maintains some of its attractiveness, although they also highlighted the less attractive aspects of it. The choices made by beginning teachers who collaborated in the study are mostly related to the dreams and aspirations when they were children and the love for teaching. It was still possible to verify that the concepts of Pedagogy and Teaching are mingle, according to the explanations given by the respondents. Although the profession no longer seen with the same perspective, the love to teach and share knowledge and information, help in building the personality of children still remains intact .